CLASSIFICATION AND REPORTING OF LONG-LIVED BIOLOGICAL ASSETS IN MALAYSIAN PUBLIC-LISTED PLANTATION COMPANIES - Mohamed, Nur Naimah; Adnan, Shayuti Mohamed (Jurnal Akuntansi dan Governance Andalas, 2024)
As home to one of the world biggest producers and exporters of palm oil and its products, the Malaysian palm oil industry is a one of the pillars of the nation pride. For nearly half a century, this industry is one of the major forces motivating political and economic stability whilst also being a prominent player in social development. Palm oil, rubber, timber and aquaculture are lead sectors with significant biological assets and are major contributors to the economy of Malaysia. These assets are critical to the export economy of the country, to employment and rural development. The objective of this study is to examine the types of biological assets reported in the financial statements of Malaysian plantation companies based on a descriptive analysis, which only serve as a basis for constructing some critical arguments regarding asset classification and reporting in an agricultural context. All companies listed on Bursa Malaysia Main Market were the sample of the study, which serves as a selection criterion to be stricter on the regulation of listed plantation companies. Discoveries demonstrate that all the 41 of public companies recorded have long-lived biological asset. In addition, over the 13-year period (2010–2022), the same few types of long-lived asset were reported by some companies while others experienced diversification through the addition of more than one additional long-lived asset. The research also finds one business that indefinitely grew with new and existing assets, one company that grew with new assets only and did not sustain previous assets and others that perpetually maintained their initial assets. By documenting these trends, this study contributes valuable insights to the literature on biological asset reporting, offering a descriptive overview of the types of long-lived assets held by plantation companies in Malaysia